الضغط النفسي وتأثيره على التوافق المدرسي لدى المراهق المتمدرس - بن صالح, هداية (University of Eloued جامعة الوادي, 2015)
يهدف البحث الحالي إلى التعرف على تأثير الضغوط النفسية على التوافق المدرسي لدى المراهق المتمدرس في المرحلة الثانوية بمدينة تلمسان، بلغت عينة الدراسة (200) تلميذ وتلميذة في المدرسة الثانوية، حيث تم الاعتماد على مقياس الضغط النفسي لعبد الحق لبوازدة-جامعة الجزائر2- والمكيف من طرف الباحثة على فئة المراهقين، ومقياس التوافق المدرسي للباحثة، توصلت الدراسة الحالية إلى نتائج كان أهمها:وجود علاقة إرتباطية سالبة بين الضغط النفسي والتوافق المدرسي ، مع وجود علاقة إرتباطية سالبة بين كل من الضغط النفسي وأبعاد التوافق المدرسي( التوافق مع الأساتذة، الزملاء، المدرسة والمادة الدراسية) وكلها كانت دالة عند مستوى (0.01)، كما أسفرت الدراسة أيضا وجود فروق ذات دلالة إحصائية بين كل من الذكور والإناث في مستوى التوافق المدرسي مع وجود علاقة إرتباطية بين التوافق المدرسي والتحصيل الدراسي Abstract: The currentre search aims to identify the impact of stress on the school compatibility with Studying Teen agerin high school in Tlemcen City.The sample of the study (200) male and female pupils in high school, where it was relying on the psychological pressure to Abdelhak Boisdh - measure of the University of Algiers 2 - and adapted from a researcher on adolescents, and the measure of school compatibility of the researcher.The current study foundThisresults:The presence of correlation between the stress of school and compatibility, and presence the correlation between each of the stress and the dimensions of the school compatibility (compatibility with teachers, colleagues school and material school), the study also resulted in the presence of statistically significant differences between both males and females in the school -level compatibility, and existence of correlation between school compatibility and academic achivemant
دراسة ميدانية في المدرسة الثانوية
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الضغط النفسي- التوافق المدرسي- المراهق المتمدرس